A data-driven digital-twin prognostics method for proton exchange membrane fuel cell remaining useful life prediction - Meraghni, Safa; Terrissa, Labib Sadek; Yue, Meiling; Ma, Jian; Jemei, Samir; Zerhouni, Noureddine (International journal of hydrogen energy, 2021)
Prognostics and health management of proton exchange membrane fuel cell (PEMFC) systems have driven increasing research attention in recent years as the durability of PEMFC stack remains as a technical barrier for its large-scale commercialization. To monitor the health state during PEMFC operation, digital twin (DT), as a smart manufacturing technique, is applied in this paper to establish an ensemble remaining useful life prediction system. A data-driven DT is constructed to integrate the physical knowledge of the system and a deep transfer learning model based on stacked denoising autoencoder is used to update the DT with online measurement. A case study with experimental PEMFC degradation data is presented where the proposed data-driven DT prognostics method has applied and reached a high prediction accuracy. Furthermore, the predicted results are proved to be less affected even with limited measurement data. •A data-driven digital twin prognostics method is proposed for PEMFCs.•A data-driven model of PEMFC is established on the digital side.•The degradation behaviour is captured via stacked autoencoders.•High prognostics accuracy is achieved with limited measurement data.